Physics of AMOC multistable regime shifts due to freshwater biases in an EMIC - A. A. Boot; H. A. Dijkstra; H. A. Dijkstra (Earth System Dynamics, 2025)
The Atlantic Meridional Overturning Circulation (AMOC), an important circulation system that modulates the global climate, has been identified as a potential tipping element. To assess AMOC tipping, climate models are used that are known to have many biases, and it is unknown how these biases affect AMOC stability. We focus here on freshwater biases over the Indian and Atlantic oceans, as identified in CMIP6 models. Next, we use CLIMBER-X, an Earth system model of intermediate complexity (EMIC), to study the effect of biases in surface freshwater flux on AMOC tipping behavior. We introduce biases in the Indian and Atlantic oceans and perform hysteresis experiments where we slowly ramp up the surface freshwater forcing in the North Atlantic until the AMOC collapses; subsequently, the forcing is reversed until the AMOC recovers again. We find that negative (positive) biases in the Indian Ocean make the AMOC more unstable (stable), whereas negative (positive) biases in the Atlantic Ocean make the AMOC more stable (unstable). When biases are introduced in both the Atlantic and Indian oceans, the tipping point associated with the AMOC collapse is hardly affected. These results show that, if the freshwater bias we applied in the Indian Ocean is larger than the one applied in the Atlantic Ocean, the AMOC is more stable in CLIMBER-X. For more reliable assessments of AMOC tipping under future emission scenarios, (freshwater) bias reduction in climate models is therefore thought to be essential.